Analisis Faktor yang Memengaruhi Kemampuan Berpikir Kritis pada Mahasiswa - Fridayani, Januari Ayu (Business Education Program of Universitas Pendidikan Indonesia, 2022)
The purpose of this study was to determine the effect of self-efficacy, time management and self-motivation on students' critical thinking skills. This study used 180 respondents who were students of the Faculty of Economics, Sanata Dharma University Batch 2020 and 2021. The method used was quantitative by distributing questionnaires, the data was processed using SPSS 25. The results of this study were that time management self-efficacy and self-motivation towards thinking skills partial critical effect on critical thinking skills.